Financial efficiency and CO2 emission in BRICS. Dose digital economy development matter? - Franley Mngumi; Li Huang; Geng Xiuli; Bakhtawer Ayub (Heliyon, 2024)
When it comes to the environmental costs, environmental economists have tried to study the effects of the foreign direct investment-growth nexus, but they have ignored the crucial role that financial development and technical innovation play. Massive increases in energy consumption have contributed to environmental degradation in the BRICS nations, which have experienced rapid IND due to their robust economies. This study uses data from 1990 to 2021 to examine the relationship between carbon emissions in BRICS member nations and factors such as FDI, technological innovation, and economic growth. Within the panel nations, the results confirm a high cross-sectional reliance. The BRICS countries' financial development, technological innovation, and foreign direct investment all have a negative and statistically significant long-run association with CO2 emissions, according to the Augmented Mean Group (AMG) estimator. On the other hand, economic growth, TI, IND, and energy use all have positive and statistically significant associations with carbon emissions. This study's researchers choose to use the Dumitrescu and Hurlin panel causality test to look at the other way around. Economic growth (EG), Digital economic growth (DEG), Financial efficiency (FE), CO2 emissions (CO2), Industrialization (IND), Technological Innovation (TI), Foreign direct investment (FDI) and Inflation are all identified as having a bidirectional long-run causative relationship. In contrast, a unidirectional causal relationship is observed between FDI and CO2 emissions. To entice high-quality FDI, the BRICS member nations must advance their industries, financial institutions, and technological innovation. In addition, these nations need immediate legislative solutions because IND is a major cause of environmental damage.